1999
DOI: 10.1002/(sici)1097-4547(19991215)58:6<823::aid-jnr9>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

4-hydroxynonenal increases neuronal susceptibility to oxidative stress

Abstract: Increased levels of reactive oxygen species occur in neurodegenerative disorders and may promote neuron death. The lipid peroxidation product 4-hydroxynonenal (HNE) is increased in neurons following oxidative stress and promotes neuron death in vitro and in vivo. The present study examined the possibility that HNE can increase neuron vulnerability to oxidative stress. Application of low concentrations of HNE (50-500 nM) increased neuron death induced by beta-amyloid or glutamate when added within 3 hr of injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Subsequently, we, showed that elevated protein-bound HNE was observed in AD brain [4, 23-25], complementing research by Markesbery and colleagues, who showed that free HNE was elevated in AD brain [26]. We also demonstrated that 3-NT was elevated in AD brain in the same regions in which protein carbonyls were elevated [27, 28].…”
Section: Alzheimer Diseasementioning
confidence: 59%
“…Subsequently, we, showed that elevated protein-bound HNE was observed in AD brain [4, 23-25], complementing research by Markesbery and colleagues, who showed that free HNE was elevated in AD brain [26]. We also demonstrated that 3-NT was elevated in AD brain in the same regions in which protein carbonyls were elevated [27, 28].…”
Section: Alzheimer Diseasementioning
confidence: 59%
“…4-HNE can impair synaptosomal membrane proteins, glutamate transport and importantly, mitochondrial functions [58,59]. Evidence indicates that 4-HNE increases neuronal susceptibility to oxidative stress [60] and serves as a mediator of oxidative stress that leads to neuronal apoptosis [61]. As indicated in the Introduction, 4-HNE has been implicated in some ocular pathological conditions [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and oligodendroglia are especially fragile under inflammatory conditions (Lehnardt et al 2003). Neurological stress provokes NF‐κB induced release of reactive oxygen species, which in turn cause neuronal vulnerability (Keller et al 1999; Hua et al 2007). A comprehensive review of microglia‐mediated inflammation and chronic excitation highlights TLR4’s contribution to neurotoxicity (Block et al 2007).…”
Section: Tlr4 Signalingmentioning
confidence: 99%